Evaluation of Sensory Marketing on Consumer Behavior: With Special Reference to Hotels in Gurugram, Haryana - Dr. Ritika Singh, Rajkiran Pund, Priya Pandey (International Journal of Advanced Science and Technology, 2020)
This is a well-known fact that the sensory organs of people are the receptors of external stimuli and presenter of the human behavior. As far as sensory marketing is concerned it is a new and evolved field of study in the area of marketing and helps the organizations to know and understand the behavior of the consumer in a better and more evolved manner.   This present study is conducted to understand the influence of sensory marketing on the behavior of consumers in hotels of Gurugram, Haryana. As we know that hotel industry is a service industry and the success of the same is dependent on the balance between the perception and expectation of the respective customers. A sample of 200 customers/visitors was taken to evaluate the scenario. This study is based on the pillars of primary data and data is collected by using a detailed and structured questionnaire. Chi square test is used to analyze the data using SPSS Ver. 22.0.